2016
DOI: 10.2147/ott.s123220
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive profile of differentially expressed circular RNAs reveals that hsa_circ_0000069 is upregulated and promotes cell proliferation, migration, and invasion in colorectal cancer

Abstract: BackgroundNowadays, despite great progress in cancer research, the detailed mechanisms of colorectal cancer (CRC) are still poorly understood. Circular RNAs (circRNAs), a new star of the non-coding RNA network, have been identified as critical regulators in various cancers, including CRC.Methods and resultsIn this study, by using unsupervised hierarchical clustering analysis, a novel dysregulated circRNA, hsa_circ_0000069, was found. The expression of hsa_circ_0000069 was measured in 30 paired CRC tissues and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
107
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 10 publications
5
107
0
Order By: Relevance
“…Yet, with the development of modern technology, people find that they are abundant in eukaryotes (Rybak‐Wolf et al, ), and are involved in many diseases, including different cancers (Hansen, Kjems, & Damgaard, ; Peng, Yuan, & Li, ; Wang et al, ). In fact, people have found that many CircRNAs were disregulated in cancers, such as CircRNA_0000069 in colorectal cancer (Guo et al, ) and CircRNA_0001649 in liver cancer (Qin et al, ), thus CircRNA can function as a biomarker for cancer (Meng et al, ; Qin et al, ; Shang et al, ; Yu et al, ). As far as we know, no report has reported the role of CircRNA_101996 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, with the development of modern technology, people find that they are abundant in eukaryotes (Rybak‐Wolf et al, ), and are involved in many diseases, including different cancers (Hansen, Kjems, & Damgaard, ; Peng, Yuan, & Li, ; Wang et al, ). In fact, people have found that many CircRNAs were disregulated in cancers, such as CircRNA_0000069 in colorectal cancer (Guo et al, ) and CircRNA_0001649 in liver cancer (Qin et al, ), thus CircRNA can function as a biomarker for cancer (Meng et al, ; Qin et al, ; Shang et al, ; Yu et al, ). As far as we know, no report has reported the role of CircRNA_101996 in cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs are a family of novel ncRNAs that play important roles in CRC tumorigenesis. For example, J. Guo et al () showed that hsa_circ_0000069 was upregulated and promoted cell proliferation, migration, and invasion in CRC. Zhu, Xu, and Chen () indicated that circBANP was overexpressed in CRC tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ciRS-7 depletion indirectly leads to a reduction of the ubiquitin conjugating enzyme UBE2A via excessive miRNA-7 in Alzheimer's disease [49]. The upregulation of hsa_circ_001569 and hsa_circ_0000069 augments cell proliferation, migration, and invasion, and hsa_circ_001988 downregulation is used as an indicator in colorectal cancer [50][51][52]. CircPVT1 was believed to be a proliferative effector and a prognostic factor based on an analysis of RNA-sequencing data in gastric cancer [53].…”
Section: Discussionmentioning
confidence: 99%